Encyclopedia of biophysics - Roberts, G. C. K. (Gordon Carl Kenmure) (Berlin ; New York : Springer, 2013)
This resource details a wide range of methods in biophysics, examining the value and the limitations of the information each provides. It also describes biophysical approaches to particular biological systems or problems.
V. 1. A-D (including 0-9) v. 2. E-I -- v. 3. J-N -- v. 4. 0-R -- v. 5. S-Z.
"Published in cooperation with the European Biophysical Societies Association (EBSA)"--Cover.
Keywords: Biophysics -- Encyclopedias